The interplay of nanocomposites co-assembly with peptide-based gels as a strategy towards on-demand drug release - Veloso, Sérgio Rafael Silva (2021)
The combination of gels with magnetic nanoparticles towards magnetic gels provides a means for the real-time remote control of gels’ properties. These properties can be further improved through the combination with liposomes as it enables the compartmentalization of drugs that can be released in a sequential and on-demand manner. However, implementing a stimulus can become a cumbersome task. Often, it requires screening different structures to obtain gels with suitable properties, and drugs might not be well encapsulated and/or cause undesirable effects on the gel’s properties. To overcome this challenge, a design strategy was developed that enabled the modulation of release of the chemotherapeutic drug doxorubicin through the interplay of (di)phenylalanine-coated magnetic nanoparticles, PEGylated liposomes and doxorubicin co-assembly in dehydropeptide-based gels.